If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(4 + -3x) = 68 (4 * 2 + -3x * 2) = 68 (8 + -6x) = 68 Solving 8 + -6x = 68 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8' to each side of the equation. 8 + -8 + -6x = 68 + -8 Combine like terms: 8 + -8 = 0 0 + -6x = 68 + -8 -6x = 68 + -8 Combine like terms: 68 + -8 = 60 -6x = 60 Divide each side by '-6'. x = -10 Simplifying x = -10
| m^2-12m+69=0 | | 35g-13=-103 | | 6*x^3-9=0 | | 6x^2-40+x=0 | | 6*x^5-9=0 | | 2u+5=-3 | | f(x)=(0.7x+6)(0.4x-8) | | 2(3x-4)=(4x+3) | | x+5=2(5x-2) | | 2(x-5)-21=0 | | 7=6(x+6)+8x | | -27=-7+4v | | 4=-7/2•5 | | 3(2x+10)=40 | | (-6x/4)=5 | | 10x+10=12x-6 | | 2+1.25=10-2.75x | | 4(7+5)=16 | | 2x-10y(-4)=20 | | x^2-5y^2+4x-10y+4=0 | | v^2-10v-96=0 | | (-27x^3)(y)/(9x^4)(y) | | 2(2g+3)=38 | | 2x-2y+5z-2x-y+3z= | | 5cosx+6cosx-8=0 | | 3^14k7/2^19 | | 2(3x+1)=4(x+5) | | P^2+20p-3500=0 | | 5(2+1)=50 | | 0.71428571y-15=5y+30 | | 5(10x+1)=12 | | 8-3x=-x-2 |